Produk-Produk Bmt Dhiya Karya Insani Terhadap Mobilitas Perdagangan di Pasar Cuplik Sukoharjo - Ahyari, Muthi'ah; , Drs. Harun, MH. (2017)
Islamic financial institutions are present as a manifestation of the development aspirations of the people who want the economic activities based on sharia principles, in addition to conventional financial institutions that have been established over the years. The Islamic financial institutions including the Islamic banks and Baitul Maal wat Tamwil (BMT) or Islamic microfinance institutions. One way to improve the economy of Indonesia in order to face the challenges of free market globalization today is to develop a creative economy based on local wisdom, which was to develop a creative economy that sells the diversity of Indonesian culture, especially in the regions as well as traders in the Market Cuplik. Through this event, is expected to know the role of BMT Dhiya Insani work in improving the mobility of Sukoharjo Clip Market trading. This study uses "field reseach" the research done in the field or arena for an occurrence directly. This research is a qualitative descriptive study. Research was conducted on the merchant market in cooperation with BMT Dhiya work Isnan Sukoharjo. Methods of data collection in studies using interviews, observations, and use documents. This study uses inductive way of thinking, which starts from facts empirically. The results of this analysis in the form of an examination of the situation under study and form a narrative description. Based on the survey results revealed that the products of BMT Dhiya Insani work towards Mobility Market Trading Cuplik Sukoharjo is in terms of buying and selling with distribution through murabaha, salam istishna, profit sharing, renting and borrowing. Factors that constrain BMT Dhiya Insani work in improving the mobility market trading Cuplik Sukoharjo is the merchant itself. Small traders using their own capital without issuing financial institution financing in order to develop the business. Keywords: small traders, market, mobility.